The Dispute Resolution Mechanism by the Cirebon District Election Supervisory Agency in the 2019 Simultaneous Elections - Nandito, Moh.; Hafizd, Jefik; Sukardi, Didi; Nurkhaerani, Ema; Harahap, Viviyen Jensifa (Strata Law Review, 2024)
The 2019 election process dispute occurred between DPD PAN Kab. Cirebon with KPU Kab. Cirebon which was submitted to Bawaslu Kab. Cirebon. The research aims to find out the legal arrangements for resolving disputes by Bawaslu Kab. Cirebon according to Law no. 7 of 2017, Bawaslu District Efforts. Cirebon is facing obstacles in the 2019 simultaneous elections, as well as the views of Siyasah jurisprudence on this matter. This qualitative research is field research with a combined empirical and normative juridical approach. Data collection techniques are observation, interviews, and documentation. The results of this research are that the resolution of election process disputes carried out in BAWASLU Cirebon Regency is regulated in Law Number 7 of 2017 concerning Elections as stated in Article 101 letter a Juncto Article 102 paragraph 3. The results of Bawaslu Kab. Cirebon, namely strengthening human resources for Bawaslu District members. Cirebon by reviewing the latest PERBAWASLU and carrying out an Adjudication simulation. The views of the fiqh siyasah institutions in the al-qadha' region and the al-hisbah region are like those of the Cirebon Regency BAWASLU. Both institutions were formed to maintain and create amar ma'ruf nahi munkar in the state administration system.